Cutaneous, gastrointestinal, hepatic, endocrine, and renal side-effects of anti-PD-1 therapy - Hofmann, Lars Georg Emre; Forschner, Andrea Lydia; Loquai, Carmen; Goldinger, Simone M.; Zimmer, Lisa; Ugurel, Selma; Schmidgen, Maria Isabel; Gutzmer, Ralf; Utikal, Jochen; Göppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al. (European journal of cancer, 2016)
Background - Anti-programmed cell death receptor-1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma as well as for other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects affect skin, gastrointestinal tract, liver, endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential. - Methods and findings - In total, 496 patients with metastatic melanoma from 15 skin cancer centers were treated with pembrolizumab or nivolumab; 242 side-effects were described in 138 patients. In 116 of the 138 patients, side-effects affected the skin, gastrointestinal tract, liver, endocrine, and renal system. Rare side-effects included diabetes mellitus, lichen planus, and pancreas insufficiency due to pancreatitis. - Conclusion - Anti-PD1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity.
Gesehen am 17.06.2019